Essential tips for the inclusive secondary classroom a road map to quality-first teaching - Whittaker, Pippa; Hayes, Rachael (Routledge, 2018)
"This go-to resource provides practitioners with quick, easy and cost-effective ways of improving inclusive practices in educational settings. Addressing the needs of children with various disabilities, from ADHD, dyslexia and low literacy skills, to physical disabilities, mental health and social needs, the book offers practitioners tips and ideas for ensuring that each and every student is integrated and supported to maximum effect."--Provided by publisher.